Failure analysis and size optimization of CFRP composite single-lap bonded joints based on the influence of multiple parameters - Kang Yang; Ziyi Liu; Xin Qi; Pengyang Li; Shude Ji; Peng Liu; Zhipeng Liu (Scientific Reports)
Abstract This paper had conducted tensile shear tests on single-lap joints (SLJs)bonded structures of carbon fiber reinforced resin matrix (CFRP) composite laminates with different overlap lengths, overlap widths, overlap model, adherend material, and adhesive layer thicknesses under two environments: room temperature dry state (RTD) and elevated temperature wet state (ETW). The failure modes were observed, and load–displacement curves were obtained. The microscopic morphology of the fracture surface was observed by scanning electron microscope (SEM). At the same time, a finite element simulation model was established to simulate the damage initiation and evolution process between layers and in the adhesive layer, and analyze the distribution laws of peel stress and shear stress in the adhesive layer. Through the combination of test data and simulation results, the influences of geometric parameters, material parameters and environmental parameters on the structure were explored, and the joint failure mechanism was revealed. Finally, the ACO-BP neural network was used to optimize the geometric parameters through test data. The research results showed that the geometric parameters of the structure mainly affect the bearing capacity and failure type. Reducing the overlap length and increasing the overlap width within a certain range can weaken the peeling phenomenon, so that a smaller overlap area has a higher shear strength. The material parameters of the adherend mainly affect the stress distribution law and stress transfer process of the adhesive layer in the overlap area. The joint mainly bore shear stress and peel stress, and shear stress is the main cause of damage initiation. When the types of adherend materials are different, the stress distribution law shows obvious asymmetric offset. The lap model mainly affects the location distribution of the failure area, and the environmental parameters mainly affect the area proportion relationship of various fracture forms in the mixed failure mode.